THE ROLE AND FUNCTION OF THE MINISTRY OF TRADE OF THE REPUBLIC OF INDONESIA IN MANAGING THE HIGH AND SCARCITY OF COOKING OIL IN INDONESIA - Junaedi (International Journal of Social Science, 2022)
Indonesia is a granary for palm oil, the largest producer of crude palm oil (CPO) in the world is still faced with the problem of oil scarcity, soaring cooking oil prices. The Role and Functions of the Ministry of Trade of the Republic of Indonesia in Overcoming the High and Scarcity of Cooking Oil in Indonesia. Data analysis was carried out using an analysis based on the Role and Functions of the Ministry of Trade of the Republic of Indonesia in Tackling the High and Scarcity of Cooking Oil in Indonesia. The purpose of this study is to examine and analyze the role and function of the Ministry of Trade of the Republic of Indonesia in Tackling the High and Scarcity of Cooking Oil in Indonesia. As for the benefits of this research academically, this research is useful regarding the role and function of the Indonesian Ministry of Trade in tackling the scarcity and skyrocketing cooking oil prices in Indonesia, while theoretically, this research can enrich the repertoire of literature in terms of studying the Role and Functions of the Indonesian Ministry of Trade) in tackling scarcity and skyrocketing cooking oil prices in Indonesia.